2014
DOI: 10.4103/2229-5178.137774
|View full text |Cite
|
Sign up to set email alerts
|

Integrated modular teaching in dermatology for undergraduate students: A novel approach

Abstract: Context:Undergraduate teaching in dermatology comprises didactic lectures and clinical classes. Integrated modular teaching is a novel approach, which integrates basic sciences with dermatology in the form of a module. Further the module also incorporates various teaching modalities, which facilitate active participation from students and promotes learning. The pre- and post-test values showed the effectiveness of the integrated module. The students feedback was encouraging.Aims:The aim of this study was to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 10 publications
2
18
0
1
Order By: Relevance
“…This transition was in accordance with previous studies that identified factors such as curriculum and examinations as fundamental for undergraduate learning 10,11. Seminars in small student groups in lieu of lectures as well as increased student involvement are the basic characteristics of this significant curriculum modification.…”
Section: Discussionsupporting
confidence: 91%
“…This transition was in accordance with previous studies that identified factors such as curriculum and examinations as fundamental for undergraduate learning 10,11. Seminars in small student groups in lieu of lectures as well as increased student involvement are the basic characteristics of this significant curriculum modification.…”
Section: Discussionsupporting
confidence: 91%
“…14 Learners can be exposed to various teaching methodologies in modules with positive students' acceptance. 7 Active learning strategies are not only supported by adult learning theories but local accreditation authorities also demand to redefine medical programmes so that students have an opportunity to develop competencies related to professionalism and medical ethics. Education experts advocate that students are more focused and motivated by learner oriented teaching when compared to traditional methods.…”
Section: Discussionmentioning
confidence: 99%
“…Modules also provide the opportunity to use various interactive modalities which seems to be more attractive to students and facilitate active learner′s participation. 7 The medical training in Pakistan is still in the process of transformation to meet the international standards of healthcare. Local health authorities have highlighted the need to replace traditional classroom teaching with more student focused approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods of teaching dermatology have been tried around the world. 2,3,4,5 Skin diseases are usually taught in specialist clinics in many countries. ese cases tend to be quite di erent from that in primary care.…”
Section: Introductionmentioning
confidence: 99%